MANAJEMEN PUSAT KEGIATAN BELAJAR MASYARAKAT - Jumrani; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2021)
The purpose of this study is to obtain a complete and clear picture of PKBM Management in PKBM Salsabila, Pasir Belengkong District, which includes planning, organizing, implementing, monitoring, and evaluating. This research uses a qualitative research approach with a case study design, the main informants are managers including the Chairperson, Secretary, treasurer, technical resource persons and tutors. Data collection is done by interview, observation, and study documentationThe results of research, management and data analysis that have been done by researchers by describing relevant theories about PKBM management are: (1). Planning of human resource tutors and staff development programs is carried out at the beginning of the new school year through workshops. (2). Organizing the tutor and employee human resource development program is done by forming a committee and division of tasks and responsibilities towards the implementation of the program. (3). Implementation of the tutor's human resource development program and has been going according to plan. (4). Supervision in the implementation of resource development programs is carried out in the field or indirectly through reports at weekly meetings. (5). Source of Funds are: (1) Operational operational assistance fund (BOP). (2) Parents' participation funds, called Monthly Mandatory Fees (IWB). (3) Kepititian funds originating from the participation of parents of students (6) The form of giving Rewards in the form of incentives from the foundation paid every month. (7). Parental support in implementing PKBM management (8). Implementation of management, in principle, does not exist, but there is a component in the management function in the development of human resources that has experienced a few constraints, namely the implementation time of activities and financing support in ideal program planning is not yet maximal.